2019
DOI: 10.1002/tox.22880
|View full text |Cite
|
Sign up to set email alerts
|

The toxic effects of titanium dioxide nanoparticles on plasma glucose metabolism are more severe in developing mice than in adult mice

Abstract: Titanium dioxide nanoparticles (TiO2 NPs) are authorized food additives, and children have the highest exposure. Therefore, children are likely more susceptible to the adverse effects of TiO2 NPs than adults. Previous study showed that oral administration of 50 mg/kg body weight (bw) TiO2 NPs increase plasma glucose in mice. However, few studies have directly compared the adverse effects of exposure to TiO2 NPs on plasma glucose metabolism of different age groups. In this study, the developing (age 3 weeks) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 32 publications
2
24
0
Order By: Relevance
“…The authors link this finding to diabetes 2 associated with high body mass index (Heller, Coffman, and Friedman 2019). On the other hand, in subchronic studies with mice exposed to TiO 2 NPs, the concentration Ti in pancreas was low compared to other organs (Hu et al 2018), or similar to the level determined in liver (Gu et al 2015, Hu et al 2020. Hence, given the very limited number of studies that either indicate high concentrations and potential effects or low concentrations and no effects, it is recommended for future studies to include determination of concentrations and effects in the pancreas.…”
Section: Additional Human Datamentioning
confidence: 93%
See 1 more Smart Citation
“…The authors link this finding to diabetes 2 associated with high body mass index (Heller, Coffman, and Friedman 2019). On the other hand, in subchronic studies with mice exposed to TiO 2 NPs, the concentration Ti in pancreas was low compared to other organs (Hu et al 2018), or similar to the level determined in liver (Gu et al 2015, Hu et al 2020. Hence, given the very limited number of studies that either indicate high concentrations and potential effects or low concentrations and no effects, it is recommended for future studies to include determination of concentrations and effects in the pancreas.…”
Section: Additional Human Datamentioning
confidence: 93%
“…In animal studies Ti levels in organs and tissues have been measured in a number of different types of animal studies (Jani, McCarthy, and Florence 1994, Wang et al 2007, Onishchenko et al 2012, Cho et al 2013, Wang et al 2013, Geraets et al 2014, Janer et al 2014, Kim and Park 2014, Tassinari et al 2014, Gu et al 2015, MacNicoll et al 2015, Mohamed 2015, Donner et al 2016, Ammendolia et al 2017, Farrell and Magnuson 2017, Kreyling et al 2017, Martins et al 2017, Hu et al 2018, Hu et al 2020, Lee et al 2019, Talamini et al 2019. Some are kinetic studies, others are general toxicity studies or studies aimed at specific effects, measuring Ti levels for different reasons (see Supplementary Information 2).…”
Section: Ti Measurements In Organs and Tissuesmentioning
confidence: 99%
“…Some studies reported increased genotoxicity in the form of DNA damage, micronuclei, and dysplastic alterations of tissues including the distal colon and liver, while others did not [15,35,[90][91][92][93][94]. Markers indicating the progression of tumors (COX-2, Ki68, p65, TNF-α, α-catenin), alteration of tumor-related pathways mitogenactivated protein kinase (MAPK) and olfactory/G-protein-coupled receptor family (GPCR) have been measured [15,88,92,95]. Changes in metabolic function, telomere shortening, TJP-1 gene expression, insulin resistance, endoplasmic reticulum (ER) stress, impaired cell cycle, and increased mitotic indices are other reported adverse effects [85,88,91,[93][94][95].…”
Section: In Vivo Toxicity Of E171mentioning
confidence: 99%
“…Markers indicating the progression of tumors (COX-2, Ki68, p65, TNF-α, α-catenin), alteration of tumor-related pathways mitogenactivated protein kinase (MAPK) and olfactory/G-protein-coupled receptor family (GPCR) have been measured [15,88,92,95]. Changes in metabolic function, telomere shortening, TJP-1 gene expression, insulin resistance, endoplasmic reticulum (ER) stress, impaired cell cycle, and increased mitotic indices are other reported adverse effects [85,88,91,[93][94][95]. Additional studies in vivo and ex vivo following i.v.…”
Section: In Vivo Toxicity Of E171mentioning
confidence: 99%
“…Notably, young individuals exposed to TiO 2 NPs are more sensitive than adults [16][17][18]. In addition, American adults are currently exposed to about 0.2-0.7 mg Ti/kg/day, while a child potentially consumes 2-4 times as much Ti as an adult amounting to 1-2 mg Ti/kg/day.…”
Section: Introductionmentioning
confidence: 99%